Reframing Women’s Public and Domestic Roles in Islam: Feminist Hermeneutics and the Qirāʾah Mubādalah Perspective - Muktazzah Fiddini; Roibin Roibin; Umi Sumbulah (Tribakti: Jurnal Pemikiran Keislaman, 2026)
Debates concerning women’s roles in public and domestic spheres remain a dynamic and contested issue within Muslim societies. This study seeks to negotiate the competing paradigms that support and oppose women’s positioning in these two domains by employing feminist hermeneutics and the qirāʾah mubādalah approach. The research adopts a historical–factual design based on a library research method. Data are collected through systematic documentation of relevant texts and analyzed using a descriptive qualitative approach, with validity ensured through source triangulation and data cross-checking. The findings indicate that a proportional reinterpretation of women’s public and domestic roles requires a transformation in mindset among both men and women, enabling each to optimize their respective potentials and contributions. Gender equality is understood not as a fixed or static endpoint, but as a dynamic and evolving condition in which men and women share balanced rights, obligations, roles, and opportunities grounded in mutual respect. The study emphasizes several foundational principles: reciprocity (mubādalah) in gender relations, the central role of education as a cornerstone of gender equality, and the synergistic relationship between public and domestic roles. Accordingly, both men and women possess the legitimate right to determine and perform roles that correspond to their capacities, potentials, and personal choices, whether within the family or in the broader social sphere.